Refugee Governance, State and Politics in the Middle East - Mencütek, Zeynep Şahin (Routledge Global Cooperation Series, 2018)
The movement of displaced people, migrants and refugees has become increasingly important around the world, leading to a need for increased scrutiny of global responses and policies towards migration. This book focuses on the Middle East, where many nations are part of this global phenomenon as both home, transit and/or host country. Refugee Governance, State and Politics in the Middle East examines the patterns of legal, political and institutional responses to large-scale Syrian forced migration. It analyses the motivations behind neighbouring countries' policy responses, how their responses change over time and how they have an impact on regional and global cooperation. Looking in particular at Turkey, Lebanon and Jordan, three of the world's top refugee hosting countries, this book explores how refugee governance differs across countries and why they diverge. To theorize variations, the book introduces multi-pattern and multi-stage refugee governance models as two complementary analytical frameworks. The book further argues that each of these three states’ refugee responses is constructed based on three main factors: internal political interests, economic-development related concerns, and foreign policy objectives as well as interactions among them. The book’s categorizations and models (on policy fields, actors, stages, patterns and driving forces) provide analytical tools to researchers for comparative analyses. Scholars and students of Comparative Politics, International Relations, Refugee Studies, Global Governance and Middle Eastern Studies will find this book a useful contribution to their fields. The Open Access version of this book, available at http://www.taylorfrancis.com, has been made available under a Creative Commons Attribution-Non Commercial-No Derivatives (CC-BY-ND) 4.0 license.